The Impact of Rice Husk Ash Waste Addition towards Landfill Stability - Meliyana Meliyana; Armia Armia; Muhammad Zardi; Cut Rahmawati (Jurnal Teknik Sipil Unaya, 2022)
Soil stability is an attempt of improvement carried out to increase soil carrying capacity in order to fulfill the needs of construction. The improvement method used in this study is mixing rice husk ash (RHA) with a certain percentage of clay soil. The tests carried out in this study include soil physical properties, compaction and CBR testing. Based on CBR testing, the results obtained were 11.65% on the variation of 0% RHA, 5% for RHA at 20.39%, 10% for RHA at 10.92% and for RHA 15% at 3.56%. The highest increase in CBR value occurred at the addition of RHA 5% which was 74.96% compared to the original soil of CBR. Based on the test results, it can be seen that the addition of waste rice husk ash with a level of 5% which is most effectively used in an effort to increase the landfill carrying capacity so that it can be functioned as a material for landfill stabilizer for subgrade roads